The influence of the revitalization of former industrial urban areas on new urban and tourism spaces: case studies of Manchester and Lyon - Kazimierczak, Jarosław (Turyzm/Tourism, 2012)
The purpose of this article is the identification of changes to urban and tourism space due to the revitalization of the industrial wastelands in selected cities of Western Europe. The first section presents problematic aspects of this issue whereas the second constitutes empirical research on two cities: Lyon and Manchester. Typical characteristics of these cities include their differing ‘tourism biographies’ as well as their diverse spatial and functional structures. Furthermore, different ways of implementing the revitalization of central area former industrial land have been followed which have been extremely significant in forming the new tourism space in both cities.